The complete mitochondrial genome sequence of Sua-type cytoplasmic male sterility of tobacco (Nicotiana tabacum). (3rd July 2016) - Li, Fengxia; Yang, Aiguo; Lv, Jing; Gong, Daping; Sun, Yuhe
Abstract: To uncover the cytoplasmic male sterility (CMS)-associated mitochondrial genes of tobacco ( Nicotiana tabacum ), we determined the complete nucleotide sequence of Sua -CMS mitochondrial genome. The Sua -CMS mtDNA sequence is 522, 731 bp in length and contains 34 protein-coding genes, 25 transfer RNA (tRNA) genes, and three ribosomal RNA (rRNA) genes. The nucleotide sequence data of 34 protein-coding genes of 14 mitochondrial genomes were used for constructing the phylogenetic tree. The results showed that Nicotiana tabacum Sua -CMS exhibits most close relationship with other solanaceae species.